2003
DOI: 10.1038/sj.bjc.6600760
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort study of the risk of colorectal and other cancers among users of low-dose aspirin

Abstract: Using data from the population-based Prescription Database of North Jutland County and the Danish Cancer Registry, we compared cancer incidence among 29 470 individuals prescribed low-dose aspirin at maximum doses of 150 mg with expected incidence based on county-specific cancer rates, during a 9-year study period. We observed 2381 cancer cases compared with 2187 expected, yielding a standardised incidence ratio (SIR) of 1.09 (95% confidence interval (CI), 1.05 -1.13). No apparent risk reductions were found fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
184
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(196 citation statements)
references
References 20 publications
(19 reference statements)
7
184
4
Order By: Relevance
“…An early stage effect appears likely, especially since aspirin has been associated with a clearly reduced risk of large-bowel adenomas that are considered a precursor of most colorectal cancers (Greenberg et al, 1993;Sandler et al, 1998). However, probably there is a threshold for the needed dose, since several studies have shown that low-dose aspirin does not have a major cancer protective effect (Friis et al, 2003). Our data also add to the literature suggesting that NSAIDs may exert an antineoplastic effect in the stomach.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…An early stage effect appears likely, especially since aspirin has been associated with a clearly reduced risk of large-bowel adenomas that are considered a precursor of most colorectal cancers (Greenberg et al, 1993;Sandler et al, 1998). However, probably there is a threshold for the needed dose, since several studies have shown that low-dose aspirin does not have a major cancer protective effect (Friis et al, 2003). Our data also add to the literature suggesting that NSAIDs may exert an antineoplastic effect in the stomach.…”
Section: Discussionmentioning
confidence: 57%
“…The details of the study design have been described earlier (Friis et al, 2003). The county is served by pharmacies equipped with a computerised accounting system from which data are sent to the Danish National Health Service, which refunds patients part of the costs associated with the purchase of drugs, including NSAIDs, prescribed by doctors, and the prescription data are transferred to the Pharmaco-Epidemiological Prescription Database (Gaist et al, 1997;Sørensen et al, 2000), including the customer's unique civil registry number, the type of drug prescribed (Gaist et al, 1997;Sørensen et al, 2000), and the date of prescription.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded retrospective analyses (Rosenberg 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003) because of potential biases in aspirin recall and selection of controls and the observed heterogeneity of results from case-control and cohort studies in previous reviews. We also excluded prospective studies that did not account for smoking (Paganini-Hill et al, 1989;Friis et al, 2003;Sorensen et al, 2003) or had no quantitative measure of aspirin use (Shreinemachers and Everson, 1994;Ratnasinghe et al, 2004) because these factors likely influence the association between aspirin and lung cancer. After exclusions, we identified nine studies that met our criteria for inclusion in the review (see Table 4).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) used in relation to lung cancer have been investigated in at least 20 studies, including four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003), fourteen cohort studies (Paganini-Hill et al, 1989;Thun et al, 1993;Schreinemachers and Everson, 1994;Langman et al, 2000;Akhmedkhanov et al, 2002;Friis et al, 2003;Holick et al, 2003;Sørensen et al, 2003;Ratnasinghe et al, 2004;Skriver et al, 2005;Hayes et al, 2006;Hernández-Diaz and Rodriguez, 2007;Jacobs et al, 2007;Wall et al, 2007) and three randomised trials (Peto et al, 1988;Lee et al, 1995;Cook et al, 2007). Significantly decreased risks were observed in three of the four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002), although all were based on selfreported drug use after diagnosis of cancer, raising the possibility of recall bias.…”
mentioning
confidence: 99%